Correlation between choroidal thickness and intraocular pressure after 23-gauge vitrectomy for idiopathic epiretinal membrane - Ishida, Masahiro (Int J Ophthalmol, 2018)
AIM: To determine the relationship between the subfoveal choroidal thickness (CT) and intraocular pressure (IOP) following idiopathic epiretinal membrane (ERM) surgery. METHODS: Retrospective observational case series of patients who had undergone 23-gauge vitrectomy for an ERM. The measurements of CT and IOP were done at the baseline and 1d, 1wk, 1, 3, 6, and 12mo after the surgery. RESULTS: Forty-four eyes of 43 patients with a mean age of 69.8±9.5y were studied. The CT was 200.8±86.3 µm at the baseline, 210.1±83.5 µm at 1d, 213.2±85.4 µm at 1wk, 203.1±84.0 µm at 1mo, 197.5±85.5 µm at 3mo, 197.7±84.0 µm at 6mo, and 191.2±86.8 µm at 12mo after surgery. The CT on day 1 and week 1 after the surgery was significantly thicker than that at the baseline CT (P=0.0023 and P<0.0001). The CT at 12mo after surgery was significantly thinner than the baseline (P=0.0062). The IOP on day 1 and week 1 were significantly lower than the baseline (P<0.0001 and P=0.0042). The IOP at 1, 3, 6, and 12mo after surgery were significantly higher than the baseline IOP (P=0.0087, P=0.0023, P<0.00051, and P<0.0001). The rates of changes in the CT between baseline and day 1 and week 1 were significantly and negatively correlated with the rates of change in the IOP (P<0.0001 and P=0.046). In the group with the IOP change rate of -30% or less at 1d postoperatively, the change rate of CT was -21.1% to 31.2% (9.8%±12.4%) and in the group of -29% or more, it was -8.9% to 28.0% (2.6%±8.9%). The change rate of CT in the group with the IOP change rate of -30% or less was significantly higher than the group of -29% or more (P=0.016). CONCLUSION: CT increases soon after the ERM surgery which is probably due to the transient hypotony, showing that IOP may be a significant confounding factor for CT.